2021
DOI: 10.1016/j.jtho.2021.01.555
|View full text |Cite
|
Sign up to set email alerts
|

P17.02 Durvalumab After chemoRadioTherapy (DART) for NSCLC Patients – a Phase II Translational and Biomarker Study

Abstract: showed a two-fold reduction in peripheral IL-8 gene expression in paired blood samples when compared with the six patients showing progressive disease with available gene expression data. Samples collected during a ceralasertib-only period prior to durvalumab treatment showed modified biomarkers of peripheral immunity including significant increases in antigen presentation gene signature and significant decreases in both exhausted T cell and NK cell signatures from bulk whole-blood RNA samples. Ceralasertib al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the ESR 1814205 CRT-IO feasibility study in poor risk and/or elderly patients with stage III NSCLC, a 18 F-FDG PET/CT is obligatory within 30 days for enrollment (NCT04441138). A phase II translational and biomarker DART study of the Norwegian group has incorporated a serial 18 F-FDG-PET/CT imaging together with collection of tumor tissue as well as blood, urine, and stool samples [38]. For the ICI as a monotherapy in advanced NSCLC, several studies have already reported about a potential of metabolic parameters to predict post-treatment progression [39,40].…”
Section: In the Cooperativementioning
confidence: 99%
“…In the ESR 1814205 CRT-IO feasibility study in poor risk and/or elderly patients with stage III NSCLC, a 18 F-FDG PET/CT is obligatory within 30 days for enrollment (NCT04441138). A phase II translational and biomarker DART study of the Norwegian group has incorporated a serial 18 F-FDG-PET/CT imaging together with collection of tumor tissue as well as blood, urine, and stool samples [38]. For the ICI as a monotherapy in advanced NSCLC, several studies have already reported about a potential of metabolic parameters to predict post-treatment progression [39,40].…”
Section: In the Cooperativementioning
confidence: 99%